2021
DOI: 10.3390/ijms222413385
|View full text |Cite
|
Sign up to set email alerts
|

A Fibrin Coating Method of Polypropylene Meshes Enables the Adhesion of Menstrual Blood-Derived Mesenchymal Stromal Cells: A New Delivery Strategy for Stem Cell-Based Therapies

Abstract: Polypropylene (PP) mesh is well-known as a gold standard of all prosthetic materials of choice for the reinforcement of soft tissues in case of hernia, organ prolapse, and urinary incontinence. The adverse effects that follow surgical mesh implantation remain an unmet medical challenge. Herein, it is outlined a new approach to allow viability and adhesion of human menstrual blood-derived mesenchymal stromal cells (MenSCs) on PP surgical meshes. A multilayered fibrin coating, based on fibrinogen and thrombin fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 73 publications
0
9
0
1
Order By: Relevance
“…Mitomycin C cytotoxicity was assessed by a viability assay using CCK-8 (Cell Counting Kit-8, Boster Biological Technology, Pleasanton, CA, USA). The protocol was carried out according to the manufacturer’s recommendations, and the absorbance at 450 nm was recorded using a Synergy™ Mx microplate reader (BioTek Instruments, Winooski-Vermont-USA) [ 21 ]. Briefly, after the first 24 h of incubation, the cell viability assay was performed with CCK-8 at T0 in two wells from each experimental group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitomycin C cytotoxicity was assessed by a viability assay using CCK-8 (Cell Counting Kit-8, Boster Biological Technology, Pleasanton, CA, USA). The protocol was carried out according to the manufacturer’s recommendations, and the absorbance at 450 nm was recorded using a Synergy™ Mx microplate reader (BioTek Instruments, Winooski-Vermont-USA) [ 21 ]. Briefly, after the first 24 h of incubation, the cell viability assay was performed with CCK-8 at T0 in two wells from each experimental group.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, absorbance was measured using a Synergy™ Mx microplate reader (BioTek Instruments, Winooski-Vermont-USA) at 450 nm. After ending the CCK-8 assay at T0, the study groups were maintained in culture on their respective plates for 3 h and 6 h at 37 °C in the HeraCell™ 150i CO 2 incubator (Thermo Scientific™, Waltham, MA, USA), with six replicates per experimental group [ 21 ]. The absorbance of formazan was measured at 450 nm using the plate reader mentioned above.…”
Section: Methodsmentioning
confidence: 99%
“…Fibrin is a natural polymer with unique biological properties useful for tissue engineering. It is an ideal cell carrier with a high ability to retain cells on the surface [1][2][3], to bind and dosed release of growth factors for supports angiogenesis and tissue repair [4,5]. Autologous fi brin can be obtained simply and in suffi cient quantities from the patient's own blood, making it a very attractive material for personalized tissue engineering [6].…”
Section: Introductionmentioning
confidence: 99%
“…Фибрин представляет собой природный полимер с уникальными для тканевой инженерии биологическими свойствами. Он является не только идеальным клеточным носителем с высокой способностью к удержанию клеток на поверхности [1][2][3], но, и благодаря способности связывать и дозированно высвобождать ростовые факторы, активно поддерживает ангиогенез и репарацию тканей [4,5]. В отличие от других биополимеров (коллагены различных типов, фибронектин, эластин), аутологичный фибрин можно просто и в достаточном количестве получать из собственной крови пациента, что делает его весьма привлекательным материалом для персонифицированной тканевой инженерии [6].…”
Section: Introductionunclassified
“… 1 , 2 , 3 , 4 However, previous studies have shown that the functional properties of MSCs would be impaired due to the aging or disease status of donors, which may significantly affect the eventual efficiency. 5 , 6 Aging is a complex, gradual, and inevitable physiological process, accompanied by the accumulation of damage macromolecules, leading to organ dysfunction and the senescence of MSCs, with the character of significantly impaired biological properties of MSCs. 7 , 8 , 9 Several methods have been tried to modify the senescence of MSCs, but the effect remains unsatisfied.…”
Section: Introductionmentioning
confidence: 99%